1998
DOI: 10.1634/theoncologist.3-5-314
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Use of Epoetin Alfa in Breast Cancer Patients

Abstract: Anemia is a common complication in cancer patients undergoing chemotherapy, and its severity depends on both the type of antineoplastic drugs and the clinical status of the patient. Breast cancer patients undergoing standard chemotherapy develop clinically significant anemia in up to 25% of cases. This percentage, moreover, increases up to 63% when more intensive chemotherapy regimens are used. The therapeutic use of erythropoietin in anemic patients, i.e., in patients with hemoglobin levels below 9‐10.5 g/dl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It also stimulates reticulocyte release from bone marrow and increases cellular hemoglobin (Hb) synthesis due to colony forming unit-erythroid (CFU-E) differentiation into erythroblast. [6][7][8][9][10] ASCO recommended that epoetin treatment should be started when the Hb level is ≥10 g/dL but also in mild anemia where the Hb level is 10-12 g/dL. The recommended dosage is 150 IU/kg, three times a week or 40,000 IU once a week.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also stimulates reticulocyte release from bone marrow and increases cellular hemoglobin (Hb) synthesis due to colony forming unit-erythroid (CFU-E) differentiation into erythroblast. [6][7][8][9][10] ASCO recommended that epoetin treatment should be started when the Hb level is ≥10 g/dL but also in mild anemia where the Hb level is 10-12 g/dL. The recommended dosage is 150 IU/kg, three times a week or 40,000 IU once a week.…”
Section: Introductionmentioning
confidence: 99%
“…5 Del Mastro and Venturini reported that in 20-40% cases of patients with Hb <10 g/dL, transfusion was still required even after epoetin alpha was given. 6 This failure may account to the delay in treatment, since epoetin response in cancer patients occurred in a range of 3-12 weeks.…”
Section: Introductionmentioning
confidence: 99%